Cementation and the hydromechanical behavior of siliciclastic aquifers and reservoirs. Issue 2 (15th November 2013) - Boutt, D. F.; Plourde, K. E.; Cook, J.; Goodwin, L. B.
Abstract Progressive cementation and lithification significantly influence the mechanical and hydrologic properties of granular porous media through elastic stiffening and permeability reduction. We use published data that quantify the effect of grain‐bridging cement distribution in granular porous media at the grain scale to investigate the influence of variable cement content on the competing roles of hydrologic and mechanical effects on fluid flow and deformation at the reservoir scale. The impact of quartz overgrowths in natural samples was quantified using a bond‐to‐grain ratio, allowing a geologically meaningful interpretation of percent cement in conceptual models of quartz cementation. An increase in the bond‐to‐grain ratio from 1 to 2.2 ( 1–15% cement by volume) results in a 1.4‐fold increase in Young's modulus and an 1000‐fold decrease in permeability. The hydromechanical properties of a suite of variably cemented natural samples are used as input into two‐dimensional, kilometre‐scale, axially symmetric poroelastic models of an isotropic confined aquifer. Models isolating the hydrologic and mechanical effects of cementation indicate that the hydrologic properties dominate the overall mechanical response, controlling both the volume and magnitude of deformation. Incorporation of changes in hydrologic properties due to cementation is therefore essential to capturing the first‐order physics of coupled aquifer behavior.